SOME OCEANOGRAPHIC FEATURES OF PELABUHANRATU BAY, WEST JAVA, INDONESIA - Helmy Akbar; Andre Wizemann; Ayu Ervinia; Haidir Ilyas; Hendra Pangkey; Kristiyanto Kristiyanto; Neira Purwanty Ismail; Singgih Afifa Putra (Universitas Bengkulu)
Pelabuhanratu Bay plays a big role for the flow of nutrients from the land to the sea of Sothern-Java. This study was conducted in Pelabuhanratu Bay, Sukabumi, West Java, in March 2012. The aim of this study is to measure the oceanographic parameters (physical and chemical) of Pelabuhanratu Bay i.e. tides, waves, current, temperature, salinity, depth, density, dissolved oxygen (DO), total suspended solids (TSS), turbidity, pH and nutrients. The bay directly faces the Indian Ocean, during the surveyed we found mean angle of wave refraction was about 4.3° ± 1.5°, with left side wind direction. Overall the current direction has an irregular trend. The tidal cycle of the bay is diurnal, with the temperature decrease into the deep layer. Only the surface exhibits a slightly lower salinity compared to the rest of the water column. Some parameters (i.e. TSS, DO) found in high concentration but declining following the depth. Other chemical concentrations (e.g. ortho-phosphate, silicate) also showed diminished after 10-15 depth measurement.